Some remarks on the definition of numbers - Palei, GK; Karu, PK (BIBECHANA, 2014)
In this paper some remarks have been given on the definition of number. It is clear that Peano’s definition of a number and Frege-Russel definition of number are not satisfactory. Number states some things about the concept and not about the counted things themselves. DOI: http://dx.doi.org/10.3126/bibechana.v11i0.10398 BIBECHANA 11(1) (2014) 165-168